Teacher’s Communication Strategies in Teaching English to Kids - Maisarah, Maisarah (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2024)
In the teaching process, appropriate communication strategies are very important in teaching children because they significantly impact their learning effectiveness. Using communication strategies that align with children's understanding level and interests, educators can facilitate good comprehension, enhance information retention, encourage active engagement, strengthen social skills, and increase children's motivation and interest in learning. This research analyzes teachers' communication strategies in this video based on Bandura's theory: Attention, Retention, Reproduction, and Motivation. This qualitative research analyzes data obtained from video on YouTube titled How to teach Kids | from a Prague kindergarten, part 1 | English for Children.